Five ways of deconstructing Europe. (March 2014) - Almond, Ian
In this essay, previous attempts to dismantle the idea of Europe as a self-contained space are briefly examined. Five strategies for deconstructing the idea of Europe are considered: re-origination, re-configuration, provincialization/de-universalization, fissuring through internal Othering and strategies of commonality. Each of these strategies, be they philosophical, philological, historical or geographical, tries to undermine the notion of 'Europe' as a self-contained space, either by alienating its origins, splitting it into alternative topographies, reducing it to just another language game, revealing its internal differences or showing how many of its features spill over into adjacent cultural spaces. The essay ends with some thoughts on what the consequences of a deconstructed Europe might be.